1992
DOI: 10.1111/j.1476-5381.1992.tb14252.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NG‐nitro‐l‐arginine methyl ester on vagally induced gastric relaxation in the anaesthetized rat

Abstract: 1 The influence of the nitric oxide (NO) biosynthesis inhibitor N0-nitro-L-arginine methyl ester (L-NAME) on the gastric relaxation induced by peripheral vagal stimulation was investigated in the anaesthetized rat.2 Peripheral vagal stimulation (10 Hz, 10 V, 1 ms for 20 s) induced a reproducible biphasic response: a short-lasting increase followed by a more pronounced decrease in intragastric pressure. This response also occurred in reserpinized animals (5mg kg-, i.p., 24 h before the experiment) while atropin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…Indeed, Lefebvre et al showed that L-NAME reduced IGP decrease during vagal nerve stimulation in anesthetized rats, indicating that NO release is crucial for this response (21). Another group showed that spontaneous antral relaxations were abolished by L-NAME (12).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Lefebvre et al showed that L-NAME reduced IGP decrease during vagal nerve stimulation in anesthetized rats, indicating that NO release is crucial for this response (21). Another group showed that spontaneous antral relaxations were abolished by L-NAME (12).…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial accommodation is primarily attributed to nutrient-driven stimulation of vagal activity, which activates enteric nitrergic pathways to relax the stomach (9,23,27,43). Thus L-NMMA blunted postprandial accommodation in healthy subjects (26,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, how GLP-1 increases gastric volumes is not understood. Since vagally mediated nitric oxide (NO) release is partly responsible for gastric accommodation (9,23,27,43), vagal inhibition would be anticipated to reduce (not increase) fasting gastric volume and postprandial accommodation. There is increasing evidence to suggest that several effects of GLP-1 [e.g., inhibition of small bowel motility (33,46) and relaxation of pulmonary arterial smooth muscle in rats (14,37)] are mediated by NO.…”
mentioning
confidence: 99%
“…72). Much of the vagal NANC inhibitory effect on the stomach is mediated by the release of nitric oxide onto gastric smooth muscle (1,10,24,37,41,44,45,68). Perfusion with CCK-8s induces an excitation in most neurons, including identified gastrointestinal-projecting DMV neurons (4,7,13,23,38,47,48,65,66,75,79).…”
Section: Discussionmentioning
confidence: 99%